O‘SMIRLIK DAVRIDA YUZAGA KELADIGAN XARAKTER AKSENTUATSIYASINING PSIXOLOGIK TA’SIR MEXANIZMLARI (Multidisciplinary Journal of Science and Technology, 2025)
this article covers the psychological mechanisms by which character accentuation whichoccurs today in adolescence, affects the deviant-behavioral formation of types, and the study of thisproblem by chetel scientists.